Contrast loading increases upper body power output in junior volleyball athletes - Smilios, I.; Sotiropoulos, K.; Barzouka, K.; Christou, M.; Tokmakidis, S. P. (Pediatric Exercise Science, 2017)
Purpose: This study examined the acute effects of contrast loading on mechanical power output during bench-press throws in junior volleyball players. Method: Eleven males (age: 16.5 ± 0.5 years) performed a contrast loading and a control protocol. The contrast protocol included the execution of 3 bench-throws with a 30% load of 1RM, after 3 min a conditioning set of 5 bench-throws with a 60% load of 1RM and after 3 and 5 min two more sets of 3 bench-throws with a 30% load of 1RM. The control protocol included the execution of 3 sets of 3 bench-throws with a 30% load of 1RM at the same time points as in the contrast protocol without the execution of the conditioning set. Results: Mechanical power with a 30% load was higher (p < .05) 3 and 5 min following the conditioning set at the contrast protocol compared with the control protocol (8.7 ± 7.5 and 10.4 ± 3.4%, respectively). High correlations (p < .05) were obtained between participant`s relative maximal strength (r = .87) and power (r = .82) and the increases in power output. Conclusion: Contrast loading increases upper body power output produced with a light load by junior athletes. The potential for increased upper body performance is more evident in stronger or more powerful individuals.